Angiotensin-Converting Enzyme Inhibitors Provide Better Long-Term Survival Benefits to Patients With AMI Than Angiotensin II Receptor Blockers After Survival Hospital Discharge. (March 2019) - Choi, In Suck; Park, Ie Byung; Lee, Kiyoung; Ahn, Tae Hoon; Kim, Ju Han; Ahn, Youngkeun; Chae, Sung-Chull; Kim, Hyo-Soo; Kim, Young Jo; Cho, Myeong Chan; Kim, Chong Jin; Jeong, Myung Ho; et al.
Aim: Renin–angiotensin–aldosterone system inhibitors (RASIs) are widely used in high-risk cardiovascular (CV) diseases, including acute myocardial infarction (AMI). However, it is not yet clear which class of RASIs provides specific benefits to patients with AMI. The present study aimed to evaluate whether angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II type 1 receptor blockers (ARBs) had any different effects on long-term CV and all-cause mortality in patients with AMI who received either agent from admission and were discharged alive from the hospital. Methods: We analyzed data of patients with AMI from the Korea Acute Myocardial Infarction Registry-National Institutes of Health registry. Cardiovascular and all-cause mortality at 12 months after AMI were assessed. Results: Among 12 481 patients with AMI who were discharged alive, RASI treatment was as follows: ACEIs (n = 5910), ARBs (n = 4009), and no RASI (n = 2562). After adjustment for multiple factors, compared with no RASI therapy, ACEI therapy was associated with lower hazard ratios (HRs) for 1-year CV and total mortality rates, whereas ARB therapy was not. In a direct comparison, compared with ARB treatment, ACEI treatment was associated with lower HRs (95% confidence interval) for CV and total mortality: 0.562 (0.420-0.753) and 0.567 (0.451-0.713), respectively. The superiority of ACEI to ARB was also observed across several subgroups. The mortality differences between the 2 treatment groups were reproduced in a propensity-score matched analysis (n = 2855 each). Conclusions: Our study of a recent AMI registry data revealed that ACEI therapy in patients with AMI was associated with better long-term survival benefits than ARB therapy.